Oral History Program Interview: Viola Elizabeth Shackelford Holliday and Grover Clevel and Holliday - Holliday, Viola Elizabeth Shackelford; Holliday, Grover Cleveland
Grover was born in Board Camp, Polk County, Arkansas in 1912 and Viola was born in Mt. Ida, Montgomery County, Arkansas in 1916. They came to Bakersfield, California on July 30, 1937. The interview consists of experiences with the WPA, living in apartments in Sunset Camp, ditch camps, the importance of church, home remedies, mechanization in the fields, racial minority relations, the 1939 cotton strike, and issues with growers and organizers.